Visualization of brainwaves using EEG to map emotions with eye tracking to identify attention in audiovisual workpieces - Silva, Thiago Henrique Coelho Tavares Da; Cavalcanti, Matheus Dantas; Sá, Felipe Melo Feliciano De; Marinho, Isaac Nóbrega; Cavalcanti, Daniel De Queiroz; Becker, Valdecir (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
This article describes a brainwave visualization system using EEG and Eye Tracking in order to map the emotional relationship of individuals with audiovisual workpieces, especially attention and taste. Using the Design Science Research method, the artifact was specified, implemented and tested with 10 subjects, using a horror movie trailer. A preliminary and a post-test questionnaire was presented to the participants. The results indicate patterns of emotional identification with the film, which can be interpreted as an inclination to watch the film in movie theaters or a repulsion to the theme/genre of the film. In conclusion, this research points to an advance in evaluation of audiovisual workpieces, contemplating unconscious emotional elements of subjective perceptions about the watched content.